Reducing the stigma of mental illness. (10th May 2016) - Stuart, H.
Abstract : This paper presents a narrative review of anti-stigma programming using examples from different countries to understand and describe current best practices in the field. Results highlight the importance of targeting the behavioural outcomes of the stigmatization process (discrimination and social inequity), which is consistent with rights-based or social justice models that emphasize social and economic equity for people with disabilities (such as equitable access to services, education, work, etc.). They also call into question large public education approaches in favour of more targeted contact-based interventions. Finally, to add to the research base on best practices, anti-stigma programs are encouraged to create alliances with university researchers in order to critically evaluate their activities and build better, evidence informed practices.